The new technological condition: From actor-centered to data-driven and future-oriented technology - Tsekeris, Charalambos; Zeri, Persefoni (Homo Virtualis, 2023)
In the ongoing process of the dynamical transformation of the knowledge basis of our contemporary society, under conditions co-shaped by the emerging “data-driven” and “future-oriented” technologies, a new logic comes to the fore, which has to do with the triumphant rise of networks and other phenomena pertaining to an enormous technological complexity. This review article turns its analytic attention on the hidden order forming the dominant model of the network society, as well as on the fundamental disruptive changes brought with the rise of information and knowledge to a central economic factor. Then, it elaborates on the preceding models of the society of individuals and the society of organizations, which were integrated in the reshaping and remodeling processes of the network society. The conclusions concern the unprecedented disconnection between the consciousness of the individuals and the domain of human experience, as well as between the specialized knowledge and the life-worlds of the citizens.